The Influence of Ethical Leadership and Organizational Culture on Organizational Commitment with Job Satisfaction as a Mediating Variable at Direktorat Jenderal Pajak (DJP) - Zauki, Imaduddin; Wolor, Christian Wiradendi; Handaru, Agung Wahyu (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to examine the influence of Ethical Leadership and Organizational Culture on Organizational Commitment, with Job Satisfaction as a mediating variable, at the Head Office of the Directorate General of Taxes (DJP) in Indonesia. Using a quantitative associative approach, data were collected from 150 functional officers through a Likert-scale questionnaire. The analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The results show that Ethical Leadership and Organizational Culture have a positive and significant effect on both Job Satisfaction and Organizational Commitment. Job Satisfaction also has a significant direct effect on Organizational Commitment and serves as a significant mediator in the relationship between Ethical Leadership and Organizational Culture with Organizational Commitment. These findings underscore the critical role of ethical values in leadership and a strong, supportive organizational culture in fostering employee satisfaction and long-term commitment. The implications suggest the importance of leadership development and cultural reinforcement strategies in public institutions to enhance performance and employee engagement.